Assessment of telomerase activity in nonsegmental vitiligo tissue: a pilot study. (31st January 2019) - Moftah, N. H.; El‐Barbary, R.; Rashed, L.; El‐Sammad, N.
Summary : Background: Vitiligo is characterized by loss of melanocytes; therefore, an increased risk of photoageing and cancer are expected. However, a low incidence of cancer and sun damage in vitiliginous skin has been reported. Telomerase is a specialized cellular enzyme catalysing the synthesis of telomeres, and an increased level of the telomerase activity has been highlighted in most of human cancer cells and cancer cell lines. Aim: To assess relative telomerase activity (RTA) among patients with nonsegmental vitiligo. Methods: In this case–control study, skin biopsy specimens were taken from 20 patients (one from lesional and another from nonlesional skin) and from sun‐protected skin from 10 healthy age‐, sex‐ and skin phototype‐matched healthy controls. PCR ELISA was performed for assessment of RTA. Results: RTA in lesional skin biopsies from patients with nonsegmental vitiligo was significantly decreased compared with nonlesional skin and healthy control skin samples, with no significant difference between the latter two. RTA in lesional skin was negatively correlated with Vitiligo Area Scoring Index but not correlated with Vitiligo Disease Activity score or RTA of nonlesional skin. Neither lesional nor nonlesional RTA levels showed any correlation with patient sex, age, skin phototype or with disease duration. Conclusion: Low levels of RTA in vitiliginous skin may help to explain the lower chance of developing skin cancer and decreased incidence of actinic damage in vitiliginous skin.